Descriptive Analysis on Leadership and Management Practices in Mental Health Hospital - Rosero, Jan Carlo Marl (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined leadership and management practices in mental health hospitals as perceived by nurses at the National Center for Mental Health. Anchored on Great Man Theory, Trait Theory, Behavioral Theory, and Contingency Theory, the study focused on collaborative, distributive, transformative, and shared leadership practices, and their relevance to quality patient care. A quantitative descriptive-correlational design was used, with 20 nurses selected through simple random sampling. Data were gathered using a validated self-made questionnaire rating scale and analyzed using weighted mean, general weighted mean, and Likert scale interpretation. Findings showed that nurses strongly agreed that collaborative leadership and distributive leadership were practiced, both with a general weighted mean of 4.6, while transformative leadership and shared leadership were also strongly evident, both with a general weighted mean of 4.7. The major barriers identified were limited financial resources, emotional and physical demands on mental health professionals, lack of specialized leadership training, staff turnover, and limited support mechanisms. The study concluded that effective leadership and management practices influence staff morale, professional development, job satisfaction, patient outcomes, and hospital performance. It recommended strengthening leadership training, participative decision-making, emotional intelligence, ethical leadership, evidence-based management, burnout prevention, staff support, and adequate resource allocation. The study supports SDG 3, SDG 8, SDG 16, and SDG 17 by promoting quality mental health care, decent work conditions, strong institutional governance, and coordinated efforts in mental health service improvement. Its sustainability impact lies in strengthening institutional, workforce, public health, and governance sustainability in mental health hospital operations.
Keywords: Collaborative Leadership; Distributive Leadership; Healthcare Management; Leadership Practices; Mental Health Hospital; National Center for Mental Health; Nurses; Patient Care; Shared Leadership; Transformative Leadership